Tolerance and Avoidance Characteristics of Prenant's Schizothoracin Schizothorax prenanti to Total Dissolved Gas Supersaturated Water. (24th July 2015) - Wang, Yuanming; Li, Kefeng; Li, Jia; Li, Ran; Deng, Yun
Abstract: When water is allowed to spill over a hydroelectric dam, the intense aeration and pressure in the deep plunge‐pool produced by the high‐volume discharge generates water supersaturated with total dissolved gases (TDGs) in areas downstream from the dam, which can cause gas bubble disease (GBD) in fish and threaten their survival. Experiments were conducted to measure the acute lethality, intermittent exposure, horizontal avoidance, and vertical avoidance of Prenant's Schizothoracin Schizothorax prenanti related to TDG supersaturation. The fish were placed in different tanks containing TDG‐supersaturated water at a maximum water depth of 35 cm, and the resulting median lethal times (LT50) determined for the fish were 23.88, 9.66, 8.74, 8.03, 4.61, 3.48, and 2.81 h when the TDG supersaturation levels were 120, 125, 130, 135, 140, 145, and 150%, respectively. The LT50 values of the fish in continuous exposure conditions were not significantly different from the LT50 values of fish subjected to intermittent exposure ( F = 2.72, df = 9, 10, P = 0.07). In all of the avoidance experiments, Prenant's Schizothoracin exhibited varying degrees of horizontal escape from and strong vertical avoidance of TDG‐supersaturated water. These results provide important information that can be used in operational processes at hydropower stations in China and contribute fundamental data for the establishment of water‐related environmental standards for this and similar species. Received November 1, 2014; accepted May 8, 2015